Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Pegawai pada Kantor Komisi Pemilihan Umum (KPU) Kabupaten Teluk Bintuni - Tohari, Bibit Imam; Lotte, Luchky N.A. (Lensa Ekonomi, 2023)
This research aims to determine the influence of leadership style and organizational culture on employee performance, both partially and simultaneously. The analysis technique used in this research is quantitative analysis. The sample in this study was 43. The sampling technique used was saturated sampling and the primary data used was a questionnaire. Secondary data obtained from journals and books related to research. The method used is multiple linear regression using SPSS statistical software. Based on the results of the analysis of the leadership style variable which partially influences employee performance, Meanwhile the organizational culture variable has no partial effect on employee performance. The results of the Anova test analysis of leadership style and organizational culture variables simultaneously influence employee performance at the General Election Commission (GEC) office of Teluk Bintuni District. Suggestions to leaders to improve their leadership style, especially in terms of respecting and appreciating subordinates, and it is necessary to further improve the organizational culture in the office, such as providing rewards and punishment for employees.